David Bentley Hart. THAT ALL SHALL BE SAVED: HEAVEN, HELL AND UNIVERSAL SALVATION - KONDYUK, Denys (Theological Reflections: Eastern European Journal of Theology, 2020)
That All Shall Be Saved: Heaven, Hell and Universal Salvation. David Bentley Hart, New Heaven, London: Yale University Press, 2019, 222 p.; ISBN 9780300246223; 26.00 USD